A Reversible Tuning of High Absorption in Chalcogenide–Metal Stacked‐Layer Structure and Its Application for Multichannel Biosensing. Issue 8 (23rd June 2021) - Behera, Jitendra K.; Liu, Kuan; Lian, Meng; Cao, Tun
Abstract : Perfect absorption ranging from visible, infrared, terahertz, to microwave is desirable for solar cell, photodetection, telecommunications, and molecular sensing. Recently, the air/dielectric–metal stacks/substrate‐based asymmetric Fabry–Pérot (FP) cavity has attracted much attention owing to lithography‐free design which is scalable and low cost. Herein, a reversibly tunable asymmetric FP cavity high absorber in the near‐infrared (NIR) region is experimentally demonstrated, relying on chalcogenide (Ge2 Sb2 Te5 )–metal (Au) stacked layers. It exhibits an extremely high absorptance of 0.99 at a resonant wavelength of 1180 nm for amorphous (AM) state; yet, the peak absorptance redshifts to 1680 nm for crystalline (CR) state. Importantly, it takes about 5 ns to reversibly transit the peak absorptance by reamorphizing the GST225. It is also experimentally shown the Brewster modes can be excited in the cavity absorber, and a wide tuning of Brewster modes (from 820 to 1500 nm) is realized as switching the state between AM and CR. The Goos–Hänchen (GH) shift can be observed at the Brewster angle for each state. For the proof of concept multibiosensing application, the cavity to detect two different solutions of the copper sulfate and glucose in both AM and CR states is numerically functionalized, respectively. Abstract : A reversible tuning of peak absorptance in asymmetric Fabry–Pérot cavity is realized for near‐infrared region, based on chalcogenide–metal stacked layers. The Brewster modes are excited in the cavity absorber and reversibly tuned as switching state between amorphous and crystal. The Goos–Hänchen shift is observed at Brewster angle for each state, showing potential for multichannel biosensing.